RISK ASSESSMENT OF HOSPITAL STRAINS FORMATION AND OCCURRENCE OF HEALTH CARE-ASSOCIATED INFECTIONS AMONG PATIENTS OF A MULTIDISCIPLINARY MEDICAL ORGANIZATION - Natalya Yu. Alekseeva; Ivan D. Zarva (Байкальский медицинский журнал)
Aim. Risk assessment of the introduction of resistant strains of microorganisms and the formation of their hospital forms in the Clinics of the Irkutsk State Medical University (Clinics of the ISMU)Materials and methods.  To analyze how the level of resistance of microbial strains isolated from patients effect the form of the disease the case histories of patients of the Clinic of the State Medical University for 2022 (n=123) were used.Bacteriological study of microbial contamination of air and environmental objects in the Clinics of the State Medical University in 2022 using swabs and aspiration method (n = 4523).Result. When comparing acute and chronic forms of diseases among groups of patients with highly resistant and low resistant strains of microorganisms, a statistically significant difference was found χ2 = 6.2 p<0.012.In 2022, in the structural subdivisions of the ISMU Clinics, positive results of washings from environmental objects were recorded in only 0.3% (95% CI 0.14 - 0.46) of studies.In the treatment room of the ENT department of the Clinic of the State Medical University in November 2022, during routine microbiological monitoring, S. aureus, which is resistant to benzylpenicillin, was isolated once. Microbiological study of biomaterial from patients of the ENT department who were hospitalized in the same period showed the presence of S. aureus which has identical resistance to antibiotics in one patient.The maximum level of resistance was registered in S. epidermidis, isolated from the biomaterial from the patient of the otorhinolaryngological department, and amounted to 88.9%.Conclusion. Chronic forms of diseases are associated with the presence of highly resistant strains of microorganisms in a patient. Given the constant circulation of resistant pathogens among patients, there is a risk of introduction and formation of hospital clones of microorganisms in medical organizations.